Activity, Purification, and Analysis of Condensed Tannins: Current State of Affairs and Future Endeavors. Issue 3 (1st May 2019) - Zeller, Wayne E.
Abstract : As a class of plant polyphenolic compounds contained in some forages (i.e., sainfoin [ Onobrychis viciifolia Scop.], big trefoil [ Lotus pedunculatus Cav.], birdsfoot trefoil [ Lotus corniculatus L.]), condensed tannins (CTs), also referred to as proanthocyanidins (PAs or PACs), exhibit a variety of biological effects on ruminants. The potential positive impact of CTs on the agricultural industry stems from their ability to modulate proteolysis during forage conservation and ruminal digestion, to prevent bloat, to reduce intestinal parasite burdens, to abate methane and ammonia emissions from ruminants, and to inhibit the activity of soil‐nitrifying bacteria. How CTs exert these effects on ruminants focuses on the interaction of CTs with proteins. The structure‐activity relationship in CT–protein interaction is not well understood but is known to be dependent on the structure and properties of both the CT and the protein. The purpose of this perspective is fivefold. First, we provide the reader with a better understanding of the structural diversity of CTs present in plant material and enable the reader to appreciate that not all CTs are the same. Second, we provide examples of how CT structural diversity affects the interaction of CTs with the protein, which, in turn, dictates the biological response from the animal. Third, we describe the hurdles in obtaining highly pure and well‐characterized CTs from natural sources for use in studies to attempt to elucidate how CTs impart each biological effect. We then describe improved and emerging techniques for CT analysis and, finally, we conclude this perspective with questions to address in future investigations and forward a list of recommendations for CT researchers to follow.